A Working Paper on the Regulatory Environment for Autonomous Vehicles - Chieppo, Charles; Giglio, Joseph M. (Archives of Business Research, 2022)
Whether it be 5, 10 or 20 years from now, fully self-driving care, also known as autonomous vehicles, are coming in the not-too-distant future. Yet despite the fact that driverless robo-taxis are already operating in some jurisdictions, there are still no federal regulations to guide their deployment. Autonomous vehicles will have – in in some places are already having – dramatic impacts on consumer mobility habits, the transportation and technology industries, and the economy as a whole. Yet despite the major disruption they represent, there are no national regulations guiding autonomous vehicle development. Instead, it is a state-by-state patchwork of regulations that guide the industry. The lack of standardization a uniform national regulatory framework would delay the development of autonomous vehicles and make it impossible for developers to achieve the the economies of scale standardization would bring – economies of scale that are critical for this new technology to be economically viable.